Internalization of Social Values Based on Local Wisdom "Sundanese Proverbs" in Social Studies Learning - Triani Widyanti; Radit Syah (Journal of Social Studies Education, 2025)
The strong character of the nation is reflected in the internalization of the noble values of local culture in people's lives. Proverbs as a form of expression of oral culture contain local wisdom that represents the moral, social, and spiritual values of a community. This research aims to identify and analyze the values of local wisdom contained in Sundanese proverbs as an effort to preserve cultural heritage and strengthen character education. The method used is a literature study with a descriptive qualitative approach, where Sundanese proverbs are classified based on the framework of universal wisdom values. The results of the analysis show that Sundanese proverbs reflect seven main values, namely: (1) spirituality and relationship with God; (2) responsibility, discipline, and independence; (3) honesty; (4) frugal and courteous living; (5) affection, care, and cooperation; (6) confidence, hard work, creativity, and never giving up; and (7) justice and leadership. These findings show that Sundanese proverbs have significant potential in supporting value-based social studies education learning, especially in student character development. Therefore, the integration of local wisdom in the curriculum is important in building the nation's cultural identity and resilience.